6(x-11)=-32

Simple and best practice solution for 6(x-11)=-32 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-11)=-32 equation:



6(x-11)=-32
We move all terms to the left:
6(x-11)-(-32)=0
We add all the numbers together, and all the variables
6(x-11)+32=0
We multiply parentheses
6x-66+32=0
We add all the numbers together, and all the variables
6x-34=0
We move all terms containing x to the left, all other terms to the right
6x=34
x=34/6
x=5+2/3

See similar equations:

| 6+4÷5b=9÷10b | | 12+4x=22+2x | | 5/6r=4+3/5 | | Y*y-13=7 | | 2/3+5=4(y-5) | | 5/6r=4-3/5 | | (7x*1.5)+(x*2)=5050 | | -4+-x/0.6=-24 | | 2x+14=(4+6) | | -4+x/0.6=-24 | | (5x*1.5)+(2*x)=5050 | | 3÷4n-18=1÷4n-4 | | x^2-6x-16=-0 | | 3*d-10=5(d-4) | | z+10+42=z+50 | | 5.6=x/2.5+-5.4 | | 2q-63=42 | | 1+5/3x=1/3+7/3x | | 2q-63=4 | | 3(2y-3)(3y+1)=2(9y-4)(y+1)-7 | | 2n+3n-8=4n-7 | | b+1÷-7=2 | | -k-`5k=-5k-4 | | 6x^2−5x+1=0 | | 50=18-a | | 8=-2/9x | | -5x+3+x=19 | | 12x^2+37x-40=0 | | 5+4*x-7=4*x+3-x* | | 4x-2x+3=9x+17 | | 5x-3x+2x=180 | | -2-3/2k=-11/4 |

Equations solver categories